Comparative Genome-Wide Alternative Splicing Analysis of Longissimus Dorsi Muscles Between Japanese Black (Wagyu) and Chinese Red Steppes Cattle - Fang, Xibi; Xia, Lixin; Yu, Haibin; He, Wei; Bai, Zitong; Qin, Lihong; Jiang, Ping; Zhao, Yumin; Zhao, Zhihui; Yang, Runjun (Frontiers in Veterinary Science, 2021)
Alternative splicing is a ubiquitous regulatory mechanism in gene expression that allows a single gene generating multiple messenger RNAs (mRNAs). Significant differences in fat deposition ability and meat quality traits have been reported between Japanese black cattle (Wagyu) and Chinese Red Steppes, which presented a unique model for analyzing the effects of transcriptional level on marbling fat in livestock. In previous studies, the differentially expressed genes (DGEs) in longissimus dorsi muscle (LDM) samples between Wagyu and other breeds of beef cattle have been reported. In this study, we further investigated the differences in alternative splicing in LDM between Wagyu and Chinese Red Steppes cattle. We identified several alternative splicing types including cassette exon, mutually exclusive exons, alternative 5′ splice site, alternative 3′ splice site, alternative start exon, and intron retention. In total, 115 differentially expressed alternatively spliced genes were obtained, of which 17 genes were enriched in the metabolic pathway. Among the 17 genes, 5 genes, including MCAT, CPT1B, HADHB, SIRT2, and DGAT1, appeared to be the novel spliced candidates that affect the lipid metabolism in cattle. Additionally, another 17 genes were enriched in the Gene Ontology (GO) terms related to muscle development, such as NR4A1, UQCC2, YBX3/CSDA, ITGA7, etc. Overall, altered splicing and expression levels of these novel candidates between Japanese black cattle and Chinese Red Steppes revealed by RNA-seq suggest their potential involvement in the muscle development and fat deposition of beef cattle.